Comparative studies of colonial architecture influences during colonization - Nge Kyaw, Ei Nge; Suhaimi, Hanis Najeha; Roslizam, Hiqmal Nurhakim; Ashari, Asyraf; Sanusi, Aliyah Nur Zafirah; Abdul Rahim, Asiah; El-Houda, Nour (KAED Universal Design Unit (KUDU), 2022)
This chapter discusses the colonization impact on architecture in Malaysia. The chapter consists of listing of colonial buildings around Masjid Jamek Sultan Abdul Samad, the Masjid in that period that was influenced by colonial architecture such as Mughal, Gothic, Moorish architecture etc,. Certain Masjid was chosen as a comparative study to Masjid Jamek Sultan Abdul Samad which are Masjid Zahir, Masjid Panglima Kinta and Masjid Ubudiah.